(untitled) (Revista de História Regional, 2008)
This research is the result of the master degree dissertation, about the local/regional history and the construction of the Paranaense identity, taking in consideration the production of the memory of the heritage buildings at Lapa/PR. It was understood that the interaction between local/regional history with the memory from the heritage buildings is directly connected to the determination of a historiographic production. The analysis had as a background the siege of Lapa episode, because it constitutes in a representative historic landmark of Paraná historiographic production, which aimed at the construction of a historic discourse of regional identification for the Paranaenses